Multi-parties key agreement protocol based on elliptic curve - Long GAO; Chun-ming TANG; Yong-qiang ZHANG (网络与信息安全学报)
The key agreement protocol is a shared key mechanism between two or more participants in a public channel.A multi key agreement protocol based on elliptic curve was designed by using the secure one-way function.The protocol was based on password authentication.The protocol designed can satisfy the security characteristics of the key exchange protocol,and has high computing efficiency.